RANCANG BANGUN PENGATUR GERAK SAMPLE CHANGER PERANGKAT RIA DENGAN MENGGUNAKAN MIKROKONTROLER AT89C51 - Riswal Nafi Siregar (BATAN, 2013)
A sample changer moving controller for RIA equipment has been designed and constructed. The controller is an electronic system that consists of AT89C51 microcontroller, driver, and its power supply circuit. A prime mover of the controller is a DC motor 12V, and the moving of the sample changer is the object to be controlled. The controller work based on an analog electronic circit system by taking benefit of the relays and transistors characteristic in use, and its mechanical controller utilizes some pressure switches. Communication of the controller with personal computer is carried out using 4 channels of port-1 at the microcontroller as the input and output of the controller. Pengatur gerak sampel changer Perangkat RIA telah dirancang bangun. Alat pengatur ini adalah peralatan elektronika yang terdiri dari mikrokontroler jenis A T89C51, rangkaian driver s dan sumber tegangan. Motor yang digunakan motor DC 12 V. Sample changer merupakan objek peranti yang hendak digerakkan. Rancang bangun rangkaian pengatur gerak sample changer ini menggunakan rangkaian analog dengan memanfaatkan fungsi-fungsi relay dan transistor. Pengatur mekanik rangkaian ini menggunakan sensor tekan. Interfacing yang dihubungkan ke PC melalui mikrokontrol menggunakan 4 jalur port 1 pada mikrokontroler sebagai input-outputnya